Exploration and bioinformatic prediction for profile of mRNA bound to circular RNA BTBD7_hsa_circ_0000563 in coronary artery disease - Ning Guo; Hanxiao Zhou; Qian Zhang; Yahong Fu; Qiaowei Jia; Xiongkang Gan; Yanjun Wang; Shu He; Chengcheng Li; Zhengxian Tao; Jun Liu; Enzhi Jia (BMC Cardiovascular Disorders, 2024)
Abstract Background As a novel circRNA, BTBD7_hsa_circ_0000563 has not been fully investigated in coronary artery disease (CAD). Our aim is to reveal the possible functional role and regulatory pathway of BTBD7_hsa_circ_0000563 in CAD via exploring genes combined with BTBD7_hsa_circ_0000563. Methods A total of 45 peripheral blood mononuclear cell (PBMC) samples of CAD patients were enrolled. The ChIRP-RNAseq assay was performed to directly explore genes bound to BTBD7_hsa_circ_0000563. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were conducted to reveal possible functions of these genes. The interaction network was constructed by the STRING database and the Cytoscape software. The Cytoscape software were used again to identify clusters and hub genes of genes bound to BTBD7_hsa_circ_0000563. The target miRNAs of hub genes were predicted via online databases. Results In this study, a total of 221 mRNAs directly bound to BTBD7_hsa_circ_0000563 were identified in PBMCs of CAD patients via ChIRP-RNAseq. The functional enrichment analysis revealed that these mRNAs may participate in translation and necroptosis. Moreover, the interaction network showed that there may be a close relationship between these mRNAs. Eight clusters can be further subdivided from the interaction network. RPS3 and RPSA were identified as hub genes and hsa-miR-493-5p was predicted to be the target miRNA of RPS3. Conclusions BTBD7_hsa_circ_0000563 and mRNAs directly bound to it may influence the initiation and progression of CAD, among which RPS3 and RPSA may be hub genes. These findings may provide innovative ideas for further research on CAD.